Economic volatility and sovereign yields’ determinants: a time-varying approach - Afonso, António (2022)
Using monthly data for 10 euro area countries between 1999:01 and 2015:12, we take a new three-step methodological approach: first, we inspect the key determinants of 10-year government bond yield spreads; second, we compute country-specific timevarying coefficient models of spreads’ determinants; third, we use these estimates as explanatory variables in panel regressions using output volatility as the dependent variable.We find that better fiscal positions or higher-than-expected economic growth prospects reduce the yield spreads,while increases in theVIX, bid-ask spread, debt-to- GDP ratio or real effective exchange rate appreciation increase the spreads.Moreover, the responsiveness of the yield spread determinants increased in the run-up to the global financial crisis. Finally, for the case of the budget balance and real growth (bid-ask spread, debt-to-GDP ratio, real effective exchange rate and VIX), the larger (higher) in absolute value the corresponding spread’s responsiveness, the lower (higher) the economic volatility.